If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(F)=10/3F+2
We move all terms to the left:
(F)-(10/3F+2)=0
Domain of the equation: 3F+2)!=0We get rid of parentheses
F∈R
F-10/3F-2=0
We multiply all the terms by the denominator
F*3F-2*3F-10=0
Wy multiply elements
3F^2-6F-10=0
a = 3; b = -6; c = -10;
Δ = b2-4ac
Δ = -62-4·3·(-10)
Δ = 156
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{156}=\sqrt{4*39}=\sqrt{4}*\sqrt{39}=2\sqrt{39}$$F_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-2\sqrt{39}}{2*3}=\frac{6-2\sqrt{39}}{6} $$F_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+2\sqrt{39}}{2*3}=\frac{6+2\sqrt{39}}{6} $
| x/4.17=100/0.6 | | 2(u-7)-3=-3(-6u+3)-6u | | 5^(2x-6)=1 | | 2(7x-23)=9x-26 | | u/3+15=23 | | –5x2–15x+20=0 | | 5x-54=-8x-93 | | 2(5x+54)=-8x+93 | | –4h−8=6+3h | | 16-64=6m | | 15x-4=145 | | 12k=45 | | 13+n=48 | | 103680=60h | | -15x5=-10x+25 | | 19x=+8 | | m/−7=2/3 | | 64m^2-1/16=0 | | 2(9x-59)=-x+34 | | 4c-60=180 | | (4a)(2a)=100 | | 4a.2a=100 | | 2^x=1÷2 | | Y=-4x^2-1+9 | | 4c–9+5=c | | 9-3(2x-7)=-22 | | 9(3x-)=9(3x+5) | | 21/4+3/4=x | | 16=-14(y+3) | | 8=5(u-2)-8u | | 111=3-6p | | 20g-1(-8g-15)=3(4g-5) |